Pemanfaatan Perpustakaan Sebagai Trend Dalam Pembelajaran Mandiri di Perguruan Tinggi - Fadli, Fadli (Program Studi Ilmu Perpustakaan UIN Alauddin, 2014)
The library is one of the forms of organization of learning resources that collects various information in the form of a book and other form (non-book material) that can be utilized by the user (faculty, students, and community) in an effort to develop their knowledge, ability and skill. Library itself is a resource center for learning. If related to teaching and learning in universities, libraries provide a very valuable contribution in the effort to increase the activity of students and improve the quality of education and teaching. Through the provision of libraries, students can interact and engage directly both physically and mentally in the learning process. Library is an integral part of the overall university programs, which together with other educational components also determine the success of the process of education and teaching. Use of the library as a trend in self-learning in higher education, must be supported by student interest in reading. Several attempts to do to improve student reading craze through the library are: 1) To provide students the literaturs they interested in ; 2) Make the library as a fun place for students through a good arrangement, with a friendly service; 3) Make the promotion and development activities interests and passions read by using the library; 4) Provide additional tasks to students outside of the classroom. Provision of additional task is certainly related to the limited hours of lessons in the classroom.